Ultrasound shear-wave elasticity and magnetic resonance diffusioncoefficient show strong inverse correlation in small fibroadenomas - (:unkn) unknown (My University, 2021)
Objective: Stiffness of breast lesions helps distinguish malignant from benign solid masses. Stiffness can be quantitatively measuredby magnetic resonance and ultrasound imaging using apparent diffusion coefficient (ADC) and shear-wave elastography (SWE)techniques, respectively. This study aims to analyze correlations between SWE and ADC in biopsy-proven small fibroadenomas.Patients and Methods: Shear-wave elastography and ADC measurements of 50 fibroadenomas were evaluated retrospectively. Meanpatient age was 41±13 years (range 27-63). All lesions had maximum diameters of ≤20 millimeters. Correlations between intralesionalADC, lesion-parenchyma ADC ratio, intralesional SWE, SWE heterogeneity index and lesion volume were analyzed.Results: Mean values of lesions were as follows: ADC=1.71±0.22 x10-3mm2/s, ADC ratio=1.04±0.09, maximum SWE=73.4±28.8kPa, minimum SWE=43.9±21.8 kPa and SWE heterogeneity index =29.4±12.7 kPa. There was a strong inverse correlation betweenfibroadenoma ADC and SWE values (rho = – 0.746, p <0.01). Significant correlations were also found between fibroadenoma volumeand ADC (rho = – 0.525, p <0.05) and SWE (rho = 0.840, p <0.01).Conclusion: Apparent diffusion coefficient and SWE values show strong inverse correlation in small fibroadenomas. If proventhreshold values for lesion characterization are revealed, ultrasonographic SWE and diffusion-weighted MRI have potential to beused interchangeably